Sustainable horizons: Navigating ESG reporting challenges in the hospitality and tourism industry - Bernard, S.; Singal, M.; Dias, Á.; Ho, J.A.; Zizka, L. (Journal of Hospitality & Tourism Research, 2025)
A review of ESG reports shows that hospitality companies often take an external, fragmented approach to ESG reporting, failing to consider the sector’s diverse stakeholder groups and unique operational challenges. A more cohesive, theoretical foundation to guide the reporting of ESG activities in the sector is necessary. Integrating stakeholder salience theory and sustainability materiality framework, the study examined the current ESG issues reported by firms in the hospitality industry, to offer preliminary directions for ESG reporting based on material ESG issues per subsector. Based on a sequential mixed-methods design, we analyzed 140 ESG reports, and followed up with a-typical structured interviews with ESG experts. We find that ESG firms across subsectors predominantly report on legislation, regulations, and salaries, with limited emphasis on stakeholder engagement. We extend the literature by including key informants’ views on effective communication of ESG, highlighting challenges, and offering recommendations to improve ESG disclosure across the industry.